S-Variant SARS-CoV-2 Lineage B1.1.7 Is Associated With Significantly Higher Viral Load in Samples Tested by TaqPath Polymerase Chain Reaction. (13th February 2021) - Kidd, Michael; Richter, Alex; Best, Angus; Cumley, Nicola; Mirza, Jeremy; Percival, Benita; Mayhew, Megan; Megram, Oliver; Ashford, Fiona; White, Thomas; Moles-Garcia, Emma; Crawford, Liam; et al.
Abstract: A SARS-CoV-2 variant B1.1.7 containing mutation Δ69/70 has spread rapidly in the United Kingdom and shows an identifiable profile in ThermoFisher TaqPath RT-qPCR, S gene target failure (SGTF). We analyzed recent test data for trends and significance. Linked cycle threshold (Ct) values for respiratory samples showed that a low Ct for ORF1ab and N were clearly associated with SGTF. Significantly more SGTF samples had higher inferred viral loads between 1×10 7 and 1×10 8 . Our conclusion is that patients whose samples exhibit the SGTF profile are more likely to have high viral loads, which may explain higher infectivity and rapidity of spread.